Actinobacteria - Basics and Biotechnological Applications 2016
DOI: 10.5772/61825
|View full text |Cite
|
Sign up to set email alerts
|

Frankia as a Biodegrading Agent

Abstract: The Frankia actinorhizal plant symbiosis plays an important role in colonization of soils contaminated with toxic aromatic hydrocarbons. Our understanding of the bacterial partner, Frankia, in the actinorhizal symbiosis has been greatly facilitated by the availability of sequenced genomes. The analysis of these Frankia genomes has suggested that these bacteria are metabolically diverse and have potential for toxic aromatic hydrocarbon degradation. In this chapter, we explore what is known about that metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
0
2
0
1
Order By: Relevance
“…The bph operon is also present in Frankia sp. strains EuI1c and EUN1f genomes 20 and was also found in the genomes of Frankia sp. strains G2 and R43 11 , 12 , cluster 3 strains isolated from Casuarina root nodules.…”
mentioning
confidence: 63%
“…The bph operon is also present in Frankia sp. strains EuI1c and EUN1f genomes 20 and was also found in the genomes of Frankia sp. strains G2 and R43 11 , 12 , cluster 3 strains isolated from Casuarina root nodules.…”
mentioning
confidence: 63%
“…Earlier studies reported that other N-fixers such as Frankia spp. were found to harbored alkane genes in addition nifH gene ( Rehan et al, 2016 ). Diazotroph capable of coupling N-fixation to hydrocarbon degradation represent a key strategy to promote plant growth in N-limited marginal lands such as PHC-contaminated soils ( Foght, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…ve Frankia sp. bakterileridir ve simbiyotik bir ilişki sonucu havadaki azotu, bitkinin bulunduğu toprağa; azot tuzu olarak bağlarlar (Vessey 2003;Karthikeyan et al 2013;Rehan et al 2016). Azot bağlayıcı bakterilere sahip bitkiler, fakir toprakları ıslah etmekte ve bitki besin maddeleri bakımından zenginleştirmektedirler (Diagne et al 2013;Stokdyk ve Herrman 2014).…”
Section: Introductionunclassified